2022
DOI: 10.1186/s12876-022-02243-8
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a nomogram for prediction of cervical lymph node metastasis in middle and lower thoracic esophageal squamous cell carcinoma

Abstract: Background Estimates of cervical lymph node (LN) metastasis in patients with middle and lower thoracic esophageal squamous cell carcinoma (ESCC) are important. A nomogram is a useful tool for individualized prediction. Methods A total of 235 patients were enrolled in this study. Univariate and multivariate analyses were performed to screen for independent risk factors and construct a nomogram to predict the risk of cervical LN metastasis. The nomog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Previous studies have indicated that T stage, histopathology, differentiation grade, tumor size, and neoadjuvant therapy are the main factors affecting LNM in EC. 7 , 14 , 15 , 16 , 17 , 18 T stage was the most crucial factor for LNM in ESCC 19 : the deeper the tumor invasion, the easier it is for the tumor cells to enter the lymphatic vessels. Consequently, LNM rates have significantly improved.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that T stage, histopathology, differentiation grade, tumor size, and neoadjuvant therapy are the main factors affecting LNM in EC. 7 , 14 , 15 , 16 , 17 , 18 T stage was the most crucial factor for LNM in ESCC 19 : the deeper the tumor invasion, the easier it is for the tumor cells to enter the lymphatic vessels. Consequently, LNM rates have significantly improved.…”
Section: Discussionmentioning
confidence: 99%
“…Our study focused on patients with ESCC of the thoracic segment with pT1 ~ 2 lymph node metastasis, which allows for further re nement of previous studies. In another analysis that predicted positive esophageal lymphadenopathy decision making, the nomogram was used to predict the likelihood of cervical lymph node metastasis from ESCC in the lower mid-thoracic region, but further studies on patient survival were lacking [15]. Other studies, exploring the clinicopathological features of pT1N0 ESCC associated with tumor recurrence and constructing a clinical prediction model to predict early recurrence [16].…”
Section: Discussionmentioning
confidence: 99%